Evaluation of the continuity of care (CoC) development model in midwifery care - Ummi Saleh; Mareta B. Bakoil; Firda Kalzum Kiah; Wahidah Sukriani; Noordiaty Noordiaty; Chendy Sofianty Pelatta (Science Midwifery, 2026)
The Continuity of Care (CoC) development model is designed to improve the quality and continuity of midwifery services during pregnancy, childbirth, the postpartum period, infant care, and contraceptive use. Ensuring that these services are safe, effective, timely, efficient, equitable, and woman-centered can enhance maternal and neonatal health outcomes. This study aimed to evaluate the implementation of the CoC development model in midwifery services. A descriptive research design was used to assess the application of the CoC development model in three health centers: Sikumana, Alak, and Bakunase. The study population consisted of midwives working in these areas, selected using purposive sampling. Data were analyzed using univariate analysis. The implementation of the CoC development model in midwifery services was carried out well, though with varying levels of achievement across the stages of care. The implementation during pregnancy was categorized as very good (14.87%), during childbirth as very good (11.30%), and during the postpartum period as good (13.42%). The CoC development model has been effectively implemented in midwifery services, contributing to improved continuity and quality of care for mothers and newborns, although further enhancement is needed to ensure consistency across all stages.